In-Situ Transesterification Of Spent Bleaching Clay Using CaO Supported On ZnO As A Basic Catalyst - Intan Shafinaz, Abd Manaf; Nurul Hajar, Embong; Mohd Hasbi, Ab. Rahim; Gaanty Pragas, Maniam (Asian Research Publishing Network (ARPN), 2016)
Shrinking fossil fuels sources, accelerating prices and the effect of its usage on the environment have indicate to the exploration for alternative fuels for diesel engines. This study focus on in-situ transesterification using barnacle shell supported on ZnO as a basic heterogeneous catalyst and spent bleaching clay as feedstock. The catalyst was characterized using XRD, FTIR, BET, FESEM and basicity. The optimum conditions for the process were: time 4 h; catalyst amount 2% (SBC weight); methanol to oil molar ratio 150:1; and co-solvent (petroleum ether to hexane, 1:1 mass ratio) with highest methyl ester content at 77 wt.%.